Randomized clinical trial of single‐ versus multi‐incision laparoscopic cholecystectomy. Issue 4 (March 2014) - Jørgensen, L. N.; Rosenberg, J.; Al‐Tayar, H.; Assaadzadeh, S.; Helgstrand, F.; Bisgaard, T.
<x xml:space="preserve">Abstract</x> Background There are no randomized studies that compare outcomes after single‐incision (SLC) and conventional multi‐incision (MLC) laparoscopic cholecystectomy under an optimized perioperative analgesic regimen. Methods This patient‐ and assessor‐blinded randomized three‐centre clinical trial compared SLC and MLC in women admitted electively with cholecystolithiasis. Outcomes were registered on the day of operation (day 0), on postoperative days 1, 2, 3 and 30, and 12 months after surgery. Blinding of the patients was maintained until day 3. The primary endpoint was pain on movement measured on a visual analogue scale, reported repeatedly by the patient until day 3. Results The intention‐to‐treat population comprised 59 patients in the SLC and 58 in the MLC group. There was no significant difference between the groups with regard to any of the pain‐related outcomes, on‐demand administration of opioids or general discomfort. Median duration of surgery was 32·5 min longer in the SLC group (P < 0·001). SLC was associated with a reduced incidence of vomiting on day 0 (7 versus 22 per cent; P = 0·019). The incidences of wound‐related problems were comparable. One patient in the SLC group experienced a biliary leak requiring endoscopic retrograde cholangiopancreatography. The rates of incisional hernia at 12‐month follow‐up were 2 per cent in both groups. Cosmetic rating was significantly improved after SLC at 1 and 12 months (P < 0·001). Conclusion SLC did not significantly diminish early pain in a setting with optimized perioperative analgesic patient care. SLC may reduce postoperative vomiting. Registration number: NCT01268748 ( http://www.clinicaltrials.gov ).